Analysis of a Reflectarray by Using an Iterative Domain Decomposition Technique - Carlos Delgado; Josefa Gómez; Abdelhamid Tayebi; Iván González; Felipe Cátedra (International Journal of Antennas and Propagation)
We present an efficient method for the analysis of different objects that may contain a complex feeding system and a reflector structure. The approach is based on a domain decomposition technique that divides the geometry into several parts to minimize the vast computational resources required when applying a full wave method. This technique is also parallelized by using the Message Passing Interface to minimize the memory and time requirements of the simulation. A reflectarray analysis serves as an example of the proposed approach.